2023
DOI: 10.1108/ijchm-04-2023-0474
|View full text |Cite
|
Sign up to set email alerts
|

MetaWOM – toward a sensory word-of-mouth (WOM) in the metaverse

Dušan Mladenović,
Elvira Ismagilova,
Raffaele Filieri
et al.

Abstract: Purpose Based on the key dimensions of the Metaverse environment (immersiveness, fidelity and sociability), this paper aims to develop the concept of sensory word-of-mouth (WOM) in Metaverse – the metaWOM. It attempts to upgrade the Reviewchain model and suggests the utilization of non-transferable tokens (NTTs) in curbing the explosion of fake WOM. Design/methodology/approach Following Macinnis’ (2011) approach to conceptual contributions, the authors browsed the currently available literature on WOM, Metav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The metaverse can be defined as a persisting and continuous multi-user realm that combines physical reality with digital virtuality, using advanced technologies, such as Virtual Reality (VR) and Augmented Reality (AR), to create multisensory interactions between individuals, digital objects and virtual environments. The metaverse has generally been conceptualized as a completely generated virtual environment (Mladenović et al, 2023) or as an extended physical reality enriched by immersive technologies (Rauschnabel et al, 2022): the present study adopts the definition of the metaverse as being a connected network of immersive environments on multi-user platforms that facilitate real-time embodied communication and dynamic engagement with digital artifacts (Mystakidis, 2022).…”
Section: The Metaverse: Opportunities and Challenges For Virtual Cult...mentioning
confidence: 99%
See 1 more Smart Citation
“…The metaverse can be defined as a persisting and continuous multi-user realm that combines physical reality with digital virtuality, using advanced technologies, such as Virtual Reality (VR) and Augmented Reality (AR), to create multisensory interactions between individuals, digital objects and virtual environments. The metaverse has generally been conceptualized as a completely generated virtual environment (Mladenović et al, 2023) or as an extended physical reality enriched by immersive technologies (Rauschnabel et al, 2022): the present study adopts the definition of the metaverse as being a connected network of immersive environments on multi-user platforms that facilitate real-time embodied communication and dynamic engagement with digital artifacts (Mystakidis, 2022).…”
Section: The Metaverse: Opportunities and Challenges For Virtual Cult...mentioning
confidence: 99%
“…Due to the novelty of the metaverse as a research concept, academic literature on its application to the customer experience is scarce (Dwivedi et al, 2023a). Existing research is mostly conceptual in nature (e.g., Buhalis et al, 2022Buhalis et al, , 2023Dwivedi et al, 2022;Go & Kang, 2023;Gursoy et al, 2022;Mladenović et al, 2023;Richter & Richter, 2023;Wong et al, 2023). Among the few empirical exceptions, in the tourism industry Tsai (2022) found that users' perceptions of holistic presence (spatial, social and self-presence) in the metaverse affected (directly and indirectly through holistic happiness) their behavioral intentions to visit a real destination.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, both academics and managers have discussed the idea of a "metaverse" or "spatial computing" future. Although we admit that these terms are still inconsistently-and often blurrily-defined, they are generally understood to refer to some sort of nextgeneration virtual (VR) and/or hybrid (AR) 3D Internet in which future consumers will spend a great deal of time (Dwivedi et al, 2022;Mladenović et al, 2023). These new environments will enable novel forms of interaction between consumers and brands, and thus, a "race for proximity" could begin.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…These new environments will enable novel forms of interaction between consumers and brands, and thus, a "race for proximity" could begin. We call for visionary research to identify these challenges early and propose-and ideally teststrategic options for brands, along with advancements in nonfungible (Hofstetter et al, 2022;Sung et al, 2023) and non-transferrable (Mladenović et al, 2023) tokens.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…It helps comprehend how storytelling influences consumer attitudes and behaviors. We argue that NTT can offer insights into consumers' emotional journey when engaging with narratives (Mladenović et al, 2023). The underlying immersive nature of storytelling then develops the transportation effect, bringing consumers into the narrative world of brands and influencing their perceptions.…”
Section: Theoretical Foundation Of Hospitality Marketing Storytelling...mentioning
confidence: 99%